The problem of rare tumors in gynecology: a clinical case of benign retroperitoneal sclerosing pelvic pecoma in 49-year-old woman - V. I. Lanchinsky; Yu. V. Chushkov; A. B. Ponomarev; Yu. I. Osmanov; A. I. Ishchenko; N. V. Vorobev (Исследования и практика в медицине)
The tumor lesions of the reproductive system organs carry the leading position in the structure of gynecological diseases. One of the rare tumors that can affect the organs of the reproductive system is pecoma, which is a tumor of mesenchymal origin. Because of it’s rare occurrence the gynecologists often misinterpret available clinical data and the results of patient`s examination, diagnosing and treating the tumor as a myoma before having received the results of the histological examination. Our article describes a clinical case of a patient who had a preliminary diagnosis of uterine fibroids, and because of this fact the planned surgical treatment was carried out. But a retroperitoneal tumor originating from the uterine vein was detected during the surgery. The diagnosis of sclerosing pecoma was established by histological and immunohistochemical studies. The article analyzes the clinical features of the patient`s disease, as well as the available results of instrumental methods of examination which can lead to final diagnosis of pecoma, also difficult issues of diagnosis and tactics of diagnostic search are noted.The literature data on the frequency of detection of pecomas, the features of their structure are presented. It is marked, that there is also a possibility of pecoma`s localization in various organs, for example, lungs, liver, kidneys, as well as in soft tissues. The possibility of multiple lesions – pecomatosis is emphasized. It is noted that among the pelvic organs the uterus is affected most often, but furthermore, the pelvic lymph nodes, the broad ligament, the omentum, the peritoneum of the pelvis and the rectum wall can be also involved in the pathological process. Risk factor of pecomas malignancy is discussed separately, the presence of three types of pecomas is determined. This fact significantly effects the probability of relapse of the tumor after surgical removal and, respectively, the tactics of postoperative follow‑up of such patients.